2018
DOI: 10.20944/preprints201806.0428.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lettuce (Lactuca sativa) handling features and coliform levels in markets of Maputo City

Abstract: Markets from Maputo City have been reported to have poorly hygienic premises and sellers unaware of the safest food handling practices. This study aimed to analyze associations between some lettuce (Lactuca sativa) handling features and the levels of total, fecal coliforms and Escherichia coli. Cabbage was purchased in the 3 markets. Just before the acquisition, the researchers recorded the source of water used to wash it, if they were sold in booths or on the floor, if they were sold mixed with other products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…These waters have not been treated as recommended, as reported by Matangue et al [ 8 ], who showed that these irrigation waters were contaminated with pathogenic bacteria and Giardia spp. Cambaza et al [ 22 ] reported the occurrence of high levels of fecal coliforms and Escherichia coli in lettuce sold in Maputo markets, probably from this producing area. Some authors emphasize that wastewater discharged from farms cannot be neglected because they are considered as an important source of water pollution, including intestinal pathogens (e.g., E. coli , G. duodenalis and Cryptosporidium spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These waters have not been treated as recommended, as reported by Matangue et al [ 8 ], who showed that these irrigation waters were contaminated with pathogenic bacteria and Giardia spp. Cambaza et al [ 22 ] reported the occurrence of high levels of fecal coliforms and Escherichia coli in lettuce sold in Maputo markets, probably from this producing area. Some authors emphasize that wastewater discharged from farms cannot be neglected because they are considered as an important source of water pollution, including intestinal pathogens (e.g., E. coli , G. duodenalis and Cryptosporidium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the way products are washed and the use of the same containers to wash all vegetables increase the possibility of contamination [ 37 ]. To reduce contamination, water must be changed frequently [ 22 ] and the containers also need to be disinfected frequently.…”
Section: Discussionmentioning
confidence: 99%